(untitled) (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2025)
Meltique beef was created by injecting vegetable oil emulsions into regular beef, but the high cost and oxidation susceptibility of canola oil limit its practicality. Palm oil, characterized by higher stability and local availability, was explored to improve physical properties and sensory qualities. The aim of this reserach was to analyze physical properties and sensory quality of roasted meltique beef injected with palm oil emulsion. Brahman cross sirloin cuts were injected with emulsions comprising oil, water, and soy protein isolate, prepared with different concentrations. The injected meats were grilled for 10 minutes and assessed for pH, texture, cooking loss, and sensory attributes. Results showed that palm oil significantly enhanced texture and sensory properties, with palm oil at higher concentration being the most similar to Wagyu beef in marbling, tenderness, and flavor. The findings indicate that palm oil was a cost-effective and stable alternative to canola oil for producing high-quality meltique beef, offering a viable solution for enhancing local beef products.